Comparison of Tympanoplasty with Temporalis Fascia and Tragal Perichondrium in Sarwari Hospital - Shah , Ghafoor; Sabirzai, Mohammad Kamil (International Journal For Research In Health Sciences And Nursing, 2021)
Objective: To compare the outcome of Temporal facia and Tragal Perichondrium in myringoplasty procedure in term graft uptake. Methodology: This was a comparative retrospective randomized control study which was conducted at Sarwari Hospital during 17 months (from 14th july, 2019 to 15th November 2020). It included sixty (13 – 56 years with mean age of 27.48±33) patients which were divided in two groups, each one having 30 patients. Temporalis fascia and tragal perichondrium were used for graft purpose in group A and group B patirents, respectively. Results: It was a comparative retrospective randomized control study which was performed in 60 patients during 17 months (from 14th july, 2019 to 15th November 2020). The age of the patients ranged 13- 56 years with mean age of 27.48±33. Overall success rate of graft uptake was noted in 28 patients (93.3%) out of 30 cases in group A and 21 paitients (70%)out of 30 cases in group B . The data were analysed in SPSS software (ver-22). The p-value less than 0.05 was considered significant. Conclusion: Temporal facia is statistically more successful as compared to tragal perichondrium in term of graft uptake in myringoplasty, so we recommend temporal facia graft for management of perforated tympanic membrane.